The Influence of Company Performance, Institutional Ownership, Managerial Ownership toward Executive Compensation (Study on Infrastructure, Utilities, and Transportation Sector Companies Listed on Indonesia Stock Exchange (BEI) 2018) - Putri, Valentine Hanis (Jurnal KIAFE, 2020)
ABSTRACTThis study aims to determine the effect of company performance, institutional ownership, and managerial ownership on executive compensation. In this study, company performance is measured by Net Profit Margin (NPM) and Return on Equity (ROE). The data in this study were obtained from the company's annual report. Data collection uses a purposive sampling method for infrastructure, utility and transportation sector companies listed on the Indonesia Stock Exchange in 2018. The samples used in this study were 29 companies from 70 companies. The analytical method of this study uses multiple linear regression analysis. The results of this study indicate that the performance of companies that are positioned with ROE, managerial ownership has a positive effect on executive compensation. While the company's performance does not affect executive compensation when measured by the NPM proxy. The institutional ownership variable in this study shows that there is an influence on executive compensation but has an inverse relationship.Keywords: Executive compensation, NPM, ROE, institutional ownership, managerial ownership.Anthony, R. N., & Govindarajan, V. (2005). Sistem Pengendalian Manajemen. Jakarta: Salemba Empat.Barkema, H. G., & Gomez-Mejia, L. R. (1998). Managerial Compensation and Firm Performance: A General Research Framework. Academy of Management Journal, 2.Barus, M. A., Sudjana, N., & Sulasmiyati, S. (2017). PENGGUNAAN RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN (Studi pada PT. Astra Otoparts, Tbk dan PT. Goodyer Indonesia, Tbk yang Go Public di Bursa Efek Indonesia). Jurnal Administrasi Bisnis.Bizjak, J., Hayes, R. M., & Kalpathy, S. (2015). Performance-Contingent Executive Compensation and Managerial Behavior .Darmadi, S. (2011). Board compensation, corporate governance, and firmperformance in Indonesia.Duffhues, P., & Kabir, R. (2008). Is the Pay-Performance Relationship Always Positive?: Evidence from the Netherlands. Journal of Multinational Financial Management.Endri, & Wakil, A. (2008). Analisis Kinerja Keuangan Dengan Menggunakan Rasio-Rasio Keuangan Dan Economic Value Added (Studi Kasus: PT. Bank Syariah Mandiri). Islamic Finance & Business Review.Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, R. D. (2015). PENGARUH STRUKTUR KEPEMILIKAN, KINERJA, DAN RISIKO TERHADAP KOMPENSASI EKSEKUTIF (Studi Empiris pada Industri Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015).Haron, H., & Akhtaruddin, M. (2013). Determinants of Directors"™ Remuneration in Malaysian Public Listed Companies. Indians Journal of Corporate Governance.Haruman, T. (2008). Struktur Kepemilikan, Keputusan Keuangan, dan Nilai Perusahaan. Finance and Banking Journal.Jensen, M. C., & Meckling, W. H. (1976). Theory of The Firm: Managerial Behavior, Agency Cost and Ownership Structure . Journal of Financial Economic.Jensen, M. C., & Murphy, J. K. (1990). Performance Pay and Top Management. Journal of Political Economy.Lazear, E., & Rosen, S. (1981). Rank-Order Tournaments as Optimum Labor Contracts. Journal of Political Economy.Maharani, W. P., & Utami, E. R. (2019). Pengaruh Kepemilikan Institusional Terhadap Kompensasi Eksekutif yang Dimediasi oleh Kinerja Perusahaan. Jurnal Reviu Akuntansi dan Keuangan.Mardiyati, U., Devi, M. S., & Suherman. (2013). PENGARUH KINERJA PERUSAHAAN, CORPORATE GOVERNANCE, DAN SHAREHOLDER PAYOUT TERHADAP KOMPENSASI EKSEKUTIF Studi Kasus Pada Perusahaan Non Financial yang Terdaftar di Bursa Efek Indonesia Tahun 2007-2010 . Jurnal Riset Manajemen Sains Indonesia (JRMSI).Munawir, S. (2007). Analisa Laporan Keuangan, Edisi Keempat. Jogjakarta: Liberty.Nazir, H. (2014). PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMPOSISI DEWAN KOMISARIS INDEPENDEN, REPUTASI KANTOR AKUNTAN PUBLIK DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA (Study Empiris pada Perusahaan Finance yang Terdaftar di Bursa Efek Indonesia) .Probohudono, A. N., Perwitasari, D., & Putra, R. P. (2016). Faktor-Faktor yang Mempengaruhi Remunerasi Direksi: Studi Komparasi Perusahaan di Australia, Ssingapura, Indonesia, dan Malaysia. Jurnal Akuntansi dan Keuangan Indonesia.Pujiningsih, A. I. (2011). PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, PRAKTIK CORPORATE GOVERNANCE DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2007-2009).Saputri, D. (2018). PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN KINERJA TERHADAP KOMPENSASI EKSEKUTIF (STUDI KASUS PADA SEKTOR INDUSTRI PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2016). Jurnal Manajemen.Scott, W. R. (2000). Financial Accounting Theory. Ontario: Prentice Hall.Sugiyono. (2008). Metode Penelitian Kuantitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2010). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Suherman, Fitriawan, R., & Ahmad, G. N. (2015). Pengaruh Kinerja Perusahaan, Kepemilikan Institusi, dan Komisaris Independen terhadap Total Kompensasi: Studi pada Perusahaan yang Terdaftar di LQ45 Tahun 2009"“2012. Jurnal Aplikasi Manajemen.Suherman, Pardede, Y. Y., & Mardiyati, U. (2016). PENGARUH KINERJA PERUSAHAAN, CORPORATE GOVERNANCE, DAN KARAKTERISTIK EKSEKUTIF TERHADAP KOMPENSASI EKSEKUTIF. Jurnal Keuangan dan Perbankan.Suherman, Rahma, W., & Buchdadi, A. D. (2010). Firm Performance, Corporate Governance, and Executive Compensation in Financial Firms: Evidence from Indonesia. working paper.Victoravich, L. M., Xu, P., & Gan, H. (2013). Institutional ownership and executive compensation Evidence from US banks during the ï¬nancial crisis. Managerial Finance.Vidyatmoko, D., Sanim, B., Siregar, H., & Didu, M. S. (2013). Faktor - Faktor yang Memengaruhi Kompensasi Eksekutif dan Dampaknya terhadap Kinerja BUMN Perkebunan .Weygandt PhD, CPA, J. J., Kimmel PhD, CPA, P. D., & Kieso PhD, CPA, D. E. (2013). Financial Accounting IFRS Edition 2e. John Wiley & Sons, Inc.Wicaksono, K. Y. (2017). PENGARUH UKURAN PERUSAHAAN, DAN KINERJA PERUSAHAAN TERHADAP KOMPENSASI EKSEKUTIF. Undergraduate Thesis, STIE PERBANAS SURABAYA.